2006
DOI: 10.1016/j.ymthe.2006.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Persistent Splice Switching by Systemically Delivered LNA Oligonucleotides in Mice

Abstract: Locked nucleic acid (LNA) oligomers were found to be very effective in their ability to modulate alternative splicing in vivo in transgenic mice that ubiquitously express a modified EGFP pre-mRNA containing an aberrantly spliced beta-globin intron (IVS2-654). Following intraperitoneal injections, the splice-switching oligonucleotide LNA SSO-654 targeted to the aberrant 5' splice site in EGFP-654 pre-mRNA corrected aberrant splicing and increased production of repaired EGFP mRNA mainly in the liver, colon, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 19 publications
1
94
0
Order By: Relevance
“…Furthermore, the resulting double-stranded structures must not be recognized by RNase H, which degrades RNA in RNA-DNA duplexes (13). These conditions are satisfied in cell culture and in vivo by modified oligomers with various backbones, including 2Ј-Omethoxyethyl phosphorothioate (MOE), locked nucleic acid (LNA), peptide nucleic acid conjugated with four lysines (PNA-4K), and phosphorodiamidate morpholino oligomers (14)(15)(16). However, MOE and LNA SSOs were ineffective at correcting aberrant splicing of IVS2-654 pre-mRNA when delivered ex vivo to cultured erythroid progenitor cells from IVS2-654 murine bone marrow cells (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the resulting double-stranded structures must not be recognized by RNase H, which degrades RNA in RNA-DNA duplexes (13). These conditions are satisfied in cell culture and in vivo by modified oligomers with various backbones, including 2Ј-Omethoxyethyl phosphorothioate (MOE), locked nucleic acid (LNA), peptide nucleic acid conjugated with four lysines (PNA-4K), and phosphorodiamidate morpholino oligomers (14)(15)(16). However, MOE and LNA SSOs were ineffective at correcting aberrant splicing of IVS2-654 pre-mRNA when delivered ex vivo to cultured erythroid progenitor cells from IVS2-654 murine bone marrow cells (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they are nontoxic and nuclease resistant (Wahlestedt et al 2000). LNAs have been reported to be extremely efficient modulators of pre-mRNA splicing (Aartsma-Rus et al 2004b;Roberts et al 2006). Ethylenebridged nucleic acids (ENA) have an ethylene bridge instead of a methylene bridge and have comparable characteristics to LNAs (Morita et al 2002(Morita et al , 2003.…”
Section: Aon Chemistrymentioning
confidence: 99%
“…A mouse model stably expressing the GFP construct has been generated, allowing easy comparison of the biodistribution of different AON analogs (Sazani et al 2002). Using this model, it was discovered that full-length LNAs generate an effect mainly in liver, colon, and small intestine after systemic delivery, thus providing a tool to manipulate splicing in these specific tissues (Roberts et al 2006). Morpholinos have gained attention for DMD exon skipping since this chemistry is taken up at higher levels by the muscle (Sazani et al 2002).…”
Section: Aon Chemistrymentioning
confidence: 99%
“…In this model, quantitative analysis of the reverse transcription-polymerase chain reaction (RT-PCR) data indicated that splice correction levels reached 40% in liver and kidney for the most effective oligonucleotide chemistries (PNAs coupled to four lysines) (Sazani et al, 2002). In another study using EGFP-654 mice, LNA oligomers achieved 85% splice correction in liver, exhibiting high potency and persistence up to 22 days after injection (Roberts et al, 2006). These promising results warrant successful application in vivo for antisense-mediated splice modulation therapy in liver associated metabolic diseases.…”
mentioning
confidence: 85%
“…In the EGFP-654 mouse described above, detailed quantification of splice switching after systemic injection showed best results for liver, colon, and intestine, while other tissues such as heart, lung, and skeletal muscle were less efficiently targeted, and no effect was observed in brain tissue (Sazani et al, 2002;Roberts et al, 2006). Other authors have shown similar results, with differences that may be explained by the different routes of delivery (intravenous or intraperitoneal), oligonucleotide chemistries, dosing regime and experimental model used (Parra et al, 2011).…”
Section: Enzyme Defects With Multisystemic Phenotypesmentioning
confidence: 99%